2013
DOI: 10.1073/pnas.1300424110
|View full text |Cite
|
Sign up to set email alerts
|

In vivo quantitative proteomics of somatosensory cortical synapses shows which protein levels are modulated by sensory deprivation

Abstract: Postnatal bilateral whisker trimming was used as a model system to test how synaptic proteomes are altered in barrel cortex by sensory deprivation during synaptogenesis. Using quantitative mass spectrometry, we quantified more than 7,000 synaptic proteins and identified 89 significantly reduced and 161 significantly elevated proteins in sensory-deprived synapses, 22 of which were validated by immunoblotting. More than 95% of quantified proteins, including abundant synaptic proteins such as PSD-95 and gephyrin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
84
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(89 citation statements)
references
References 108 publications
5
84
0
Order By: Relevance
“…whole tissue punch vs synaptoneurosomes, respectively, the molecules linked to brain disorders also differ substantially in the protein classes they encompass ( Figure 7). For example, cytoskeletal proteins make up a large portion of the diseaserelated targets identified by Butko et al (Butko et al, 2013) and transcription factors are not found, whereas the reverse Figure 7. Experience-dependent plasticity and select brain disorders share common molecular targets.…”
Section: ) From Synaptic Plasticity To Synaptic Disordersmentioning
confidence: 93%
See 4 more Smart Citations
“…whole tissue punch vs synaptoneurosomes, respectively, the molecules linked to brain disorders also differ substantially in the protein classes they encompass ( Figure 7). For example, cytoskeletal proteins make up a large portion of the diseaserelated targets identified by Butko et al (Butko et al, 2013) and transcription factors are not found, whereas the reverse Figure 7. Experience-dependent plasticity and select brain disorders share common molecular targets.…”
Section: ) From Synaptic Plasticity To Synaptic Disordersmentioning
confidence: 93%
“…Because RNA translation into protein is not a linear process, and controlled by posttranscriptional regulatory mechanisms (Keene, 2007), proteomic studies will be required to mechanistically address the molecular pathways associated with expression of plasticity. Currently the only proteomics study available in barrel cortex was performed by Butko and colleagues (Butko et al, 2013), who either clipped or brushed the whisker pads of rats for a period of 30 days, starting from P4, and subsequently prepared synaptoneurosomes from barrel cortex. Using tandem mass spectrometry Butko and colleagues identified systematic downregulation of translation for various ion channels (e.g.…”
Section: 2) Extended Sensory Stimulation and Deprivation And Their mentioning
confidence: 99%
See 3 more Smart Citations